Growing Up Together without Trauma: A Community Service Educational Program for Children and Adolescent Mental Health - Alika Da’ja Anagovi; Netti Ermawati; Umi Nurjanah (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
The mental health of children and adolescents is a crucial foundation for building a resilient and character-driven generation. This Community Service Program (KKN) implemented two primary intervention programs focused on mental health issues in two different locations. At SDN Soroyudan, the "Growing Together Without Bully" program was conducted to enhance the understanding and critical awareness of 6th-grade students regarding the dangers of bullying through interactive education and a symbolic anti-bullying declaration. Meanwhile, in Jogonegoro Village, the "Healthy Emotions, Great Teens" program was designed to equip adolescents with emotional regulation skills through training, enabling them to face life's challenges in a healthy and productive manner. The implementation methods included interactive lectures, discussions, simulations, and symbolic activities that encouraged active participant engagement. Evaluation results indicated a significant increase in students' and adolescents' understanding of bullying issues and emotional management, alongside the establishment of a collective commitment to creating a safe and supportive environment. These programs demonstrate that an educational approach addressing emotional and social aspects can positively impact the mental health of children and adolescents. Program sustainability is highly recommended through cross-sector collaboration to foster a healthy and inclusive educational ecosystem.